People’s Perception on Climate Change: The Context of Local and Global Discourse - Khatri, Bishnu Bahadur; Pasa, Rajan Binayek (Asian Journal of Population Sciences, 2023)
Climate change has become a significant threat to mankind in recent years. For the development of various adaptation strategies, it is essential to comprehend how people perceive climate change and its indicators. With this consideration, climate change is a glocal problem and discourse that is both global and local in nature. The paper attempts to discuss and analyse on people’s perception on climate change in both local and global contexts. This study is empirical in nature and is based on a review of the literature on how people perceive climate change at all scales, from local to global. For this purpose, systematic review method is used to analyse and discuss the electronic databases of literature search that was extracted by web based search engines. Among 232 literatures identified, 45 most relevant articles were selected for systematic review. The study indicates that the majority of people experienced and strongly perceived changes in climatic factors and events. Most of the local people perceived significant increase in climate change indicators in recent years and faced various level of impacts both local to global context. However, the climate change has affected on livelihood of the people living everywhere. As a result, it is crucial to focus on enhancing locals' capacity to cope to changing climate. The perceived knowledge and understanding of people on climate change can be helpful to cope with the potential risks and challenges of climate change in the future.